DESIGN OF CONTROL AND MONITORING OF BRUSHLESS DIRECT CURRENT (BLDC) MOTOR ON CONVEYOR USING BLUETOOTH BASED ON STM 32 - Hadi Saputro, Teguh; Faizah, Fiqqih; Silk Moonlight, Lady (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
DC motors are one of the most popular motors used in the industrial world. In operation, DC motors use a direct current (DC) source. In its application, the BLDC motor is combined with a method to make it easier to control the BLDC motor to match what is desired, one example is the Proportional Integral Derivative (PID) method, which is a control consisting of a standard configuration of Kp, Ki, and Kd whose values are determined in order to get the desired result or speed, namely speed with good stability with a small error rate and overshoot. The control system for the BLDC stepper motor nema 17 on the conveyor uses the STM32 Nucleo F030R8 module as a microcontroller and the HC-05 bluetooth module as a remote control interface on the conveyor motor. To send commands from the microcontroller to the motor, a driver is needed which is used as a data receiver and control setting from the microcontroller, namely the L298N motor driver. The monitoring system on the miniature conveyor uses an LM393 speed sensor as a stepper motor rotation speed reader and an INA219 sensor as a current and voltage reader. Sensor readings will be processed on the microcontroller and the results will be displayed on the 1.3-inch LCD screen that has been installed. In this study, it is still in prototype form, so the miniature conveyor cannot receive too heavy a load. The load is adjusted to the torque capacity of the BLDC stepper motor used, which is 0.36 N.m. In other words, the maximum miniature conveyor receives a load with a stable speed of less than or equal to 2 kg, because the load on the conveyor belt will affect the speed of the BLDC motor. With this research, it is hoped that it can be a lesson about control and monitoring systems on BLDC motors. The maximum Bluetooth range is 9 meters.